THE EFFECT OF SUGAR TYPE AND ITS CONCENTRATION IN THE FERMENTATION MEDIUM OF SACCHAROMYCES CEREVISIAE ON ERGOSTEROL LEVELS - Peterson, William
Saccharomyces cerevisiae is a yeast commonly used in alcoholic fermentation and utilizes monosaccharide and disaccharide sugars as an energy source to produce ergosterol and ethanol. Ergosterol is the main sterol found in yeast, has important functions, and can be used in research as a marker of fungal cell health and in industrial applications such as making products, for example the synthesis of vitamin D2. In this research, Saccharomyces cerevisiae was fermented in a medium containing sugar (glucose or fructose) as the main carbon source. Glucose and fructose are simple sugars that are classified as monosaccharides and are often found in fruit, although these two sugars enter the metabolic pathway at different points. The yeast was given treatment first before being allowed to ferment. The yeast was rejuvenated and passaged twice, then seeded and entered into the fermentation process. The fermentation process was carried out for 36 hours using several sugar concentrations (1%, 2%, 3%, 5%, 7% and 10%), then the ergosterol produced was extracted. In the extraction process, dissolution optimization was carried out between chloroform and n-hexane, and it was concluded that chloroform had a better ability to extract ergosterol than n-hexane. Verification of the analytical method using a UV-Vis spectrophotometer was also carried out with several parameters such as specificity, linearity, precision and accuracy whose values are determined. The results of the verification process showed that all parameters met the requirements based on USP 40. The samples were then analyzed for levels using verified methods. This research shows that the ergosterol levels produced using sugar or fructose as a sugar source are not significantly different. Ergosterol levels were optimum with an average of 23 µg/mL for glucose media and 23.53 µg/mL for fructose media with a sugar concentration of 5%.